A synthesized view of the CSF-blood barrier and its surgical implications for aging disorders - Taha, Birra; McGovern, Robert; Lam, Cornelius (Frontiers in Aging Neuroscience, 2025)
In this review, we explore the mechanisms of the blood-cerebrospinal fluid (CSF) barrier and CSF transport. We briefly review the mathematical framework for CSF transport as described by a set of well-studied partial differential equations. Moreover, we describe the major contributors of CSF flow through both diffusive and convective forces beginning at the molecular level and extending into macroscopic clinical observations. In addition, we review neurosurgical perspectives in understanding CSF outflow pathways. Finally, we discuss the implications of flow dysregulation in the context of neurodegenerative diseases and discuss the rising role of perivascular drainage pathways including glymphatics.